KETOASIDOSIS DIABETIK DI DIABETES MELITUS TIPE 1 - Zuhrinah Ridwan; Uleng Bahrun; Ruland DN Pakasi R (Indonesian Association of Clinical Pathologist and Medical laboratory, 2016)
Type 1 Diabetes Mellitus (DMT1) is an autoimmune disease characterized by impaired carbohydrate, protein and lipid metabolismresulting in insulin deficiency either absolute or relative. The absolute insulin deficiency found in DMT1, is caused by a defect in thepancreatic ß cells leading to a defect in insulin synthesis by the pancreas gland. In this article, a case of type 1 DM in a child withketoacidosis diabetes has been reported. The diagnosis was based on classical symptoms, blood glucose level, C-peptide, metabolic acidosisand keton uria. The case reported is a 12 year old girl, with main complaints of 9 kg body weight loss since three (3) years ago. Thepatient always felt hungry, thirsty and was frequently urinating. In her family history no such case was denied. The patient had beentreated in the district general hospitals for five (5) days and was diagnosed as type 1 diabetes mellitus and was then referred to the Dr.Wahidin Sudirohusodo Hospital. The laboratory test results revealed as follows, random glucose level was 729 mg/dL, arterial blood gasanalysis showed metabolic acidosis, C-peptide was 0.1 ng/mL and urinalysis showed 150 mg/dL protein, 1000 mg/dL glucose, 150 mg/dL ketone and 250 RBC/uL. The patient was diagnosed as type 1 diabetes mellitus with diabetic ketoacidosis and received 0.5 U/kg/dayinsulin therapy. This case report aimed to determine the type 1 diabetes mellitus in a child is accompanied by diabetic ketoacidosis.